Pengaruh Penambahan Methanol Terhadap Performa Mesin Injeksi 150 CC Berbahan Bakar Pertamax - fatkhurrozak, faqih; Lukman Sanjaya, Firman; Syarifudin, Syarifudin; Nur Akhmadi, Amin; Budhi Hendrawan, Andre (P3M Politeknik Negeri Cilacap, 2025)
The use of fossil fuels causes air pollution in Indonesia. Biofuel is one of the alternatives often used, one of which is methanol. Methanol has efficient characteristics and low emissions, increases engine performance and thermal efficiency, and reduces fuel consumption. This study aims to observe the concentration of pertamax - methanol addition of 5%, 10%, and 15% on performance, BSFC, and BTE. The percentage of pertamax and methanol fuel mixing is 5%, 10%, and 15%, and the speed used is 1000, 2000, and 3000 rpm. The measurements taken are power, BSFC, and BTE using a dynotest and displayed on a screen. Adding 5%, 10%, and 15% methanol to pertamax increases engine performance. The addition of Pertamax-methanol PM15 increases power by 25% at a speed of 1000 rpm, reduces BSFC by 40% on PM15 at a speed of 2000 rpm, and increases thermal efficiency on PM5 by 73% at a speed of 2000 rpm